Primary Cutaneous Umbilical Melanoma: The Michigan Experience. Issue 3 (March 2020) - Charles, Kristy B.; Chan, May P.; Smith, Noah R.; Orsini, Amy P.; Noh, Iris K.; Kozlow, Jeffrey H.; Johnson, Timothy M.; Cha, Kelly B.
Abstract : BACKGROUND: Primary cutaneous umbilical melanoma is rare. Thorough information regarding its characteristics and treatment, including use of sentinel lymph node biopsy (SLNB) staging, is difficult to obtain. The unique anatomy of the umbilicus adds to the complexity of diagnosing and treating melanoma at this site. OBJECTIVE: To improve understanding of diagnosis and treatment of primary cutaneous umbilical melanoma through presenting 7 new cases and reviewing 39 cases in the literature. MATERIALS AND METHODS: The University of Michigan melanoma database query and review of the literature regarding reported cases of primary umbilical melanoma. RESULTS: In 7 new and 39 previously reported cases of primary cutaneous umbilical melanoma, we describe signs and symptoms, histopathologic features, differential diagnosis, relevant anatomical considerations, and definitive treatment including SLNB when applicable. CONCLUSION: Our series, combined with a thorough literature review and compilation of findings, provides a better understanding and appreciation of melanoma in the unique anatomical site of the umbilicus, with a reminder to carefully examine the umbilicus during a full skin examination in patients at risk of melanoma. Primary umbilical melanoma presents and can be appropriately treated similarly to cutaneous melanoma in other sites, with attention to relevant anatomy.